Circular economy in agriculture: unleashing the potential of integrated organic farming for food security and sustainable development - Selvan, Thiru; Panmei, Lumgailu; Murasing, Kiran Kumar; Guleria, Vipan; Ramesh, Karuppanan Ramasamy; Bhardwaj, D. R.; Thakur, C. L.; Kumar, Dhirender; Sharma, Prashant; Digvijaysinh Umedsinh, Rathod; Kayalvizhi, D.; Deshmukh, Harshavardhan K. (Frontiers in Sustainable Food Systems, 2023)
Food is a basic human requirement which sustains the dynamics of the Earth’s inhabitants by satisfying hunger, providing nutrition, health and catering to culture, tradition, and lifestyle. However, rising global population coupled with climate change including calamities, diseases, conflicts, as well as poor agricultural practices put a huge constraint on the quantity and quality of food. Modern agriculture propelled by green revolution has somehow been able to meet the food requirements of the ever-increasing population being heavily dependent on chemical fertilizers, pesticides, and machinery, reducing the quality of food, and simultaneously posing a great risk of environmental quality degradation and genetic diversity reduction. The Integrated Organic Farming Systems (IOFS) is a novel approach that holds potential in addressing the challenge of reconciling food production with environmental preservation. As this approach embraces zero or minimal chemical use; adopting the reprocessing and reuse of agricultural residues has led to a sustainable system that can be viewed as the closest approach to nature and circular economy. However, certain constraints need to be addressed, such as ascertaining the effectiveness of organic fertilizers, the complexities associated with weed management, and the inadequacy of proficiency, financial resources, and technical expertise required to implement the IOFS. Therefore, this paper emphasizes the comprehensive benefits that could be derived from IOFS, particularly agroforestry, including efficient food productivity, improved food quality, biodiversification of crops by the adoption of lesser-known crops to cater to cultural requirements and minimal capital input to achieve environmental sustainability and a carbon neutral economy.